Pengaruh Media Sosial Terhadap Terungkapnya Kasus Bullying di SMA Binus Serpong - Ardiana, Oktavia Dwi; Narindra, Rochella Amalia; Syah, Aurellia Zerikha; Azzahra, Dinda; Prasetyo, Handoyo (Media Hukum Indonesia (MHI), 2024)
This study discusses the impact of social media on the revelation of bullying cases at Binus Serpong High School. Social media has become a significant platform for spreading information and revealing incidents of bullying among teenagers. This study employs a normative juridical method to analyze how social media can accelerate the process of uncovering and handling bullying cases, as well as its impact on the community and the school administration. The results of the research show that social media is effective in raising awareness and facilitating quick responses to bullying cases. Additionally, social media also provides emotional support for victims through anti-bullying campaigns and online communities. However, there are risks of information misuse and the potential occurrence of cyberbullying. Schools are expected to take transparent and fair actions in following up on bullying cases by coordinating with the police and the Indonesian Child Protection Commission (KPAI). This study recommends increasing education about bullying, providing psychological support, and implementing strict anti-bullying policies within the school environment.